In vivo localization of iron starvation induced proteins under variable iron supplementation regimes in Phaeodactylum tricornutum - Kazamia, Elena; Mach, Jan; McQuaid, Jeffrey B; Gao, Xia; Coale, Tyler H; Malych, Ronald; Camadro, Jean-Michel; Lesuisse, Emmanuel; Allen, Andrew E; Bowler, Chris; Sutak, Robert (Plant direct, 2022)
UNLABELLED: The model pennate diatom Phaeodactylum tricornutum is able to assimilate a range of iron sources. It therefore provides a platform to study different mechanisms of iron processing concomitantly in the same cell. In this study, we follow the localization of three iron starvation induced proteins (ISIPs) in vivo, driven by their native promoters and tagged by fluorophores in an engineered line of P. tricornutum. We find that the localization patterns of ISIPs are dynamic and variable depending on the overall iron status of the cell and the source of iron it is exposed to. Notwithstanding, a shared destination of the three ISIPs both under ferric iron and siderophore-bound iron supplementation is a globular compartment in the vicinity of the chloroplast. In a proteomic analysis, we identify that the cell engages endocytosis machinery involved in the vesicular trafficking as a response to siderophore molecules, even when these are not bound to iron. Our results suggest that there may be a direct vesicle traffic connection between the diatom cell membrane and the periplastidial compartment (PPC) that co-opts clathrin-mediated endocytosis and the "cytoplasm to vacuole" (Cvt) pathway, for proteins involved in iron assimilation. Proteomics data are available via ProteomeXchange with identifier PXD021172. HIGHLIGHT: The marine diatom P. tricornutum engages a vesicular network to traffic siderophores and phytotransferrin from the cell membrane directly to a putative iron processing site in the vicinity of the chloroplast.
Keywords: iron; iron starvation induced proteins; siderophores; proteome; fluorescent proteins; diatoms; P. tricornutum